Effects of Hyperthyroidism on Contractility and Na+/Ca2+ Exchanger Activity in the Isolated Papillary Muscle of Rats - Rambo,Angela Mara (2022)
Abstract Background: Hyperthyroidism (Hy) is an endocrine disorder, in which the thyroid hormones markedly alter the cardiac function. Increased myocardial contractility and cardiac output, improvement in diastolic relaxation, changes in electrical activity, increments in ventricular mass, and arrhythmias have been reported. However, the influences of thyroid hormones upon molecular mechanisms of cardiac functions have not yet been fully understood. Objectives: To evaluate changes in cardiac contractile parameters and the Na+/Ca2+ exchanger (NCX) function in induced hyperthyroid rats. Methods: Hy was induced by intraperitoneal injections of T3 (15 μg/100 g) for 10 days. Contractile parameters and NCX function were evaluated in the isolated papillary muscle. Data normality was confirmed by the Shapiro-Wilk test. The comparison between groups was performed through an unpaired Student’s t-test. Results are expressed as mean ± SD. The accepted significance level was p < 0.05. Results: Our data revealed, in the Hy group, an increase of 30.98% in the maximum speed of diastolic relaxation (–284.64 ± 70.70 vs. –217.31 ± 40.30 mN/mm2/sec (p = 0.027)) and a boost of 149% in the NCX function in late phase of relaxation (20.17 ± 7.90 vs. 50.22 ± 11.94 minutes (p = 0.002)), with no changes in the maximum twitch force (p = 0.605) or maximum speed of systolic contraction (p = 0.208) when compared to the control. Conclusion: The improvement in relaxation parameters is hypothetically attributed to an increase in Sarco-Endoplasmic Reticulum Ca2+ATPase isoform 2 (SERCA2) expression and an increased calcium flow through L-type channels that boosted the NCX function.